2015
DOI: 10.2196/jmir.4312
|View full text |Cite
|
Sign up to set email alerts
|

Association of Online Health Information–Seeking Behavior and Self-Care Activities Among Type 2 Diabetic Patients in Saudi Arabia

Abstract: BackgroundHealth information obtained from the Internet has an impact on patient health care outcomes. There is a growing concern over the quality of online health information sources used by diabetic patients because little is known about their health information–seeking behavior and the impact this behavior has on their diabetes-related self-care, in particular in the Middle East setting.ObjectiveThe aim of this study was to determine the online health-related information–seeking behavior among adult type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
127
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 23 publications
21
127
0
3
Order By: Relevance
“…Our study found that Google was the most commonly used Internet search engine (55.8%) to obtain health-related information as found in previous work from Saudi Arabia on patients with type 2 diabetes patients, where Google was used by 98% of the studied population[26]. Some participants in our study reflected their aversion to using the Internet as a source of collecting health-related information.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our study found that Google was the most commonly used Internet search engine (55.8%) to obtain health-related information as found in previous work from Saudi Arabia on patients with type 2 diabetes patients, where Google was used by 98% of the studied population[26]. Some participants in our study reflected their aversion to using the Internet as a source of collecting health-related information.…”
Section: Discussionsupporting
confidence: 71%
“…It would be useful to collect more data on socio-economic, educational background, health literacy and demographics to see whether these have any links to the sources that are used for health-information seeking as previous studies have shown that these characteristics may influence behavior[31]. Also, it would be useful to collect information on the language the health information is searched for on the Internet as Jamal and colleagues found a majority of their participants searched in Arabic only[26]. …”
Section: Discussionmentioning
confidence: 99%
“…Estimates of how many people utilize the Internet for health information vary approximately between 30 and 80% [2,3,[7][8][9][10], and it is worth examining the patients' "online journey" via which they discover OHI. Many studies suggest an initial reliance on search engines to identify relevant websites [9,11,12]. Subsequently, patients use individual criteria to filter which websites are worth exploring [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, patients' perceptions of the reliability and trustworthiness of websites is important, since this impacts on their decisions regarding their own management. Indeed, concerns have been expressed that patients often obtain inaccurate, outdated, outright false, or even potentially life-threatening online information [12,[14][15][16]. We need to comprehend the information needs that drive patients to utilize this medium; conversely, why is it that some patients choose not to use this seemingly widely available and easy-to-access resource?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation